Detection of ipaH gene in Large Plasmid of Escherichia coli Isolated from Different Sources of Bangladesh - Akhter, Fahmina; Fakruddin, M; Azmuda, Nafisa; Begum, Anowara; Birkeland, Nils Kare; SKhan, Sirajul Islam; Akhter, Humaira (Bangladesh Journal of Microbiology, 2012)
Large plasmid (more than 100 MDa) plays a significant role in Escherichia coli virulence as many virulent genes including the ipaH are encoded by large plasmids. Characterization of such large plasmid of E. coli from different sources based on ipaH gene has not yet been reported with success and credible reproducibility in Bangladesh. Forty E. coli isolates of environmental, clinical, avian, and mammalian sources were examined to detect the presence of large plasmids. Among them, plasmids recovered from 32 isolates were found to range between 100 and 145 MDa in size. Antibiotic susceptibility pattern of the isolates against 17 different antibiotics showed that most of them were resistant to more than 6 antibiotics and thus were designated multiple antibiotic resistant (MAR) strains. Out of 32 isolates, 10 were (3 clinical, 5 environmental, 1 avian and 1 mammalian source) found to possess a gene product of 423 bp size after PCR assay from plasmid DNA. Southern hybridization was carried out with ipaH probes and the results revealed the presence of band of correct size in both large plasmid DNA and in chromosomal DNA. Presence of the appropriate gene product in newly discharged environmental E. coli strains questions the credibility of using these bacteria as an indicator of water pollution in tropical countries like Bangladesh. The innovative approaches employed in this investigation regarding characterization of large plasmid based on the presence of ipaH gene in E. coli isolates from environmental, clinical, avian and mammalian sources opened up avenues for challenging research in future. DOI: http://dx.doi.org/10.3329/bjm.v28i2.11822 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 84-87